Cerkvi na Homcu in v Šmarci - Lavrič, Ana (Opera Instituti Artis Historiae, 2019)
Of the Gothic church which was erected at Homec after the miraculous apparition of the Blessed Virgin in 1419 only the lower part of the free-standing bell-tower has been preserved up to this day~in the times of Turkish incursions around 1500 it was adapted to serve as a defence tower as well. Since the condition of the old church had worsened and the building had also become too small, a new sanctuary was built on its northern side in 1723, and the next year the church was pulled down and a new nave was begun on its site~the building was completed in 1728.